Breath-Holding Spells, Erythroblastopenia, & Iron - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
An 8-month-old boy with a 1-month history of breath-holding spells and erythroblastopenia is reported from the Naval Medical Center, San Diego, CA.